Desarrollo de una guía práctica dirigida a los migrantes ecuatorianos, radicados en España que se acogen al menaje de casa - Chafla Parrales, Carlota Mirela (2016)
In Ecuador the high oil prices caused revenues are invested in the public sector, progressively demanding skilled and unskilled Ecuadorians living in the country and in other countries of the world work. The Government was violated the rights of Ecuadorian residents in Spain when the banks began to foreclose on their property; and under such circumstances the return of migrants with their household goods, consisting of tax exemptions for goods used in the home, car and team to decide to return voluntarily to the country it was encouraged. Today Ecuadorians living in Spain, do not have a guide to inform migrants of the resolutions issued the National Customs Service of Ecuador (SENAE) on the process to be followed and changes that occur in the context legal of household goods. From these facts it was proposed to develop a practical guide that allows indicate the processes to be followed by migrants residing in Spain and who choose to live in Ecuador definitively, returning with their household goods, vehicle and team……